Fresh air funds and functional families: The enduring politics of race, family and place in juvenile justice reform. (November 2015) - Cox, Alexandra
This article examines the enduring ways that racial politics are masked by discourses of place and family in the history of juvenile justice in the USA. The tropes of place and family have been invoked since the inception of the USA's juvenile justice system and have influenced the processes of policing, removal, and return, even as the latest incarnation of reforms focus on building juvenile justice facilities and alternatives to incarceration within urban areas. By pointing to recent manifestations of this rhetoric in New York, the article identifies the thread that links these claims together: the desire by social control agents for submission by the primarily impoverished and young people of color who defy legal authority.